Electrospray and MALDI Mass Spectrometry : Fundamentals, Instrumentation, Practicalities, and Biological Applications. - Cole, Richard B. (John Wiley & Sons, 2010)
Discover how advances in mass spectrometry are fueling new discoveries across a broad range of research areas. Electrospray and MALDI Mass Spectrometry brings both veteran practitioners and beginning scientists up to date with the most recent trends and findings in electrospray ionization and matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. In particular, this Second Edition highlights how advances in electrospray and MALDI mass spectrometry are supporting important discoveries in new and emerging fields such as proteomics and metabolomics as well as in traditional areas.